The great tradition in english literature from Shakespeare to Shaw - Rubinstein, Annette T (New York : Modern Reader Paperbacks, 1969)
The Elizabethan age, 3. -- William Shakespeare, 20. -- Francis Banco, 80. -- Puritans and cavaliers, 111. -- John Milton, 121. -- The restoration, 163. -- John Bunyan, 170. -- The age of reason, 206. -- The augustans, 206. -- Jonathan Swift, 224. -- Daniel Defoe, 251. -- Henry Fielding, 287. -- From the augustans to the romantics, 315. -- Jone Austen, 328. \
v.1: William Shakespeare to Jane Austen. -- v.2: Robert Burns to Bernard Shaw